Development of Nursing Diagnosis & Intervention Instrument Based on Standardized Nursing Language (Nanda-I, NOC,NIC) - Diana Rachmania; Nursalam Nursalam; Esti Yunitasari (Jurnal Ners, 2016)
Introduction: Nursing documentation appropriate standards of nursing language (Standarized Nursing Language), was still a problem in the nursing profession, especially uniformity in using nursing diagnoses and interventions language. Instrument were needed to produce a good quality of nursing diagnosis and intervention’s documentation. The purpose of the research was to develop nursing diagnosis and interventions instrument based on the Standardized Nursing Language (NANDA-I, NOC, NIC).Methods: This study was action reserach carried out in 2 phases. The population of phase 1 were 16 participants and 9 samples. Participants and samples selected by purposive sampling techniques with participants were 15 and samples were 7. The population of phase 2 was 13 participants and 8 samples. Participants and samples selected by purposive sampling technique with participants were 13 and samples were 8. Analyze data using descriptive analysis, statistical analysis using Pearson Product Moment Correlation for validity test and Cronbach alpha for reliability test.Results: Development of nursing diagnostic and interventions instruments, that was formulated based on Focus Group Discussion, declared valid and reliable.Discussion: Each hospital was expected to always routinly evaluate the nursing diagnosis and interventions instrument as a standard and policies in order to create a quality nursing documentation.